A Systematic Review of Preoperative Fatty Infiltration and Rotator Cuff Outcomes. Issue 2 (July 2016) - Khair, M. Michael; Lehman, Jason; Tsouris, Nicholas; Gulotta, Lawrence V.
Background: Fatty infiltration (FI) of the muscle as graded by the Goutallier classification (GC) is a well-known sequela following rotator cuff injury. The degree to which this predicts the success of rotator cuff repair is unknown. Questions/Purposes: We conducted a systematic review to address the following questions: (1) Does the grade of FI of the rotator cuff muscles present preoperatively predict retear rates postoperatively? (2) Are amounts of preoperative FI predictive of functional outcomes following repair? Methods: Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and the Cochrane Central Register of Controlled Trials online databases were searched for all literature published between January 1966 and March 2015. Keywords were chosen to achieve a broad search category. All articles were reviewed by three of the authors, and those meeting the study inclusion criteria were selected for data abstraction. Results: The systematic literature review yielded 11 studies reporting on a total of 925 shoulders. Rotator cuffs with moderate or significant FI preoperatively (grades 2–4) had a significantly higher retear rate than those with no or minimal FI (grades 0–1) (59 vs. 25%, p  = 0.045). Four studies reported postoperative Constant scores and preoperative GC scores. One study found that lower GC scores were associated with higher Constant scores postoperatively, one found no association, and the data was inconclusive in the other two. Conclusions: While lower preoperative GC scores are associated with lower rates of rotator cuff retear following repair, there is insufficient data to make conclusions on the effects of FI on functional outcomes following repair.